Philippines : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update to the Report on the Observance of Standards and Codes on Fiscal Transparency Module for the Philippines. The clear separation of fiscal and public enterprise management in the Philippines has been reduced somewhat by the rising losses of the National Power Corporation (NPC). The decline in the ratio of revenue to GDP in recent years continues to highlight the need for more published information on special tax incentives provided to the private sector, particularly with regard to the fiscal costs.